Perinatal Mental Health Care for Women With Severe Mental Illness During the COVID-19 Pandemic in India—Challenges and Potential Solutions Based on Two Case Reports - Nagendrappa, Sachin; Vinod, Pratibha; Pai, Naveen Manohar; Ganjekar, Sundarnag; Desai, Geetha; Kishore, M. Thomas; Thippeswamy, Harish; Vaiphei, Kimneihat; Chandra, Prabha S. (Frontiers in Global Women's Health, 2021)
The ongoing COVID-19 pandemic in India has created several challenges in the care of women with perinatal mental illness. Access to healthcare has been disrupted by lockdowns, travel restrictions, and the unavailability of outpatient services. This report aims to discuss the challenges faced by women with severe mental illnesses during the perinatal period with the help of two case reports. Accordingly, we have highlighted the role of COVID-19 infection as a traumatic event during childbirth and its role in triggering a psychotic episode in women with vulnerabilities; difficulties faced by women with postpartum psychosis in accessing perinatal psychiatry services; and the challenges of admission into an inpatient Mother-Baby Unit (MBU). Further, we have discussed potential solutions from the perspectives of Lower and Middle-income (LAMI) countries that need to be extended beyond the pandemic. They include offering video consultations, reviewing hospital policies, and evolving strategies to mitigate traumatic experiences for pregnant and postpartum women with severe mental illnesses in both obstetric and psychiatric care.